EXPRESSÃO TRANSCRICIONAL DA ENZIMA POLIGALACTURONASE (PG) EM MORANGOS CV. CAMAROSA SUBMETIDOS À IRRADIAÇÃO Gama - Tiecher, Aline; Vicenzi, Raul; Severo, Joseana; Silva, Jorge A. (Salão do Conhecimento, 2013)
Resumo